2022
DOI: 10.3390/s22239447
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Lens Stray Light with Regard to the Incapacitation of Imaging Sensors—Part 2: Validation

Abstract: Recently, we developed a simple theoretical model for the estimation of the irradiance distribution at the focal plane of commercial off-the-shelf (COTS) camera lenses in case of laser illumination. The purpose of such a model is to predict the incapacitation of imaging sensors when irradiated by laser light. The model is based on closed-form equations that comprise mainly standard parameters of the laser dazzle scenario and those of the main devices involved (laser source, camera lens and imaging sensor). How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In an earlier work, we compared the calculated spatial light distribution in the focal plane of a camera lens, based on our theoretical model, with the output of the optical design software FRED [ 25 ]. We showed that the results of our theoretical model are comparable with the simulated results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier work, we compared the calculated spatial light distribution in the focal plane of a camera lens, based on our theoretical model, with the output of the optical design software FRED [ 25 ]. We showed that the results of our theoretical model are comparable with the simulated results.…”
Section: Discussionmentioning
confidence: 99%
“…For details, we refer the reader to Reference [ 18 ]. For this generic set of scatter parameters, we use capital letters: The scatter parameters were validated by simulations with the FRED optical design software [ 25 ]. In Equation (A3), a fourth scatter parameter, , is listed.…”
Section: Appendix A1 Damage Thresholds Of Image Sensorsmentioning
confidence: 99%
“…One simulation was focused on the diffraction component and the second one on the stray light component. The output of both simulation runs was then combined and subsequently compared with calculations based on Equation (4); for detail see reference [11]. Some results are presented in Figure 8.…”
Section: Validation Using the Optical Design Software Fredmentioning
confidence: 99%
“…In this publication, we summarize our work on laser safety calculations for electro-optical imaging systems, which was presented in detail in several journal articles [8][9][10][11]. This includes the derivation of equations to estimate exposure limits (Section 4) and dazzle spot sizes (Section 5), approximations to estimate hazard distances (Section 6), suggestions for values of non-standard parameters (Section 7) and the validation of the this work by modeling and field trials (Section 8).…”
Section: Introductionmentioning
confidence: 99%
“…In this publication, we review our work on laser safety calculations for electro-optical imaging systems, which was presented in detail in several journal articles and conference proceedings 8 12 This includes the derivation of equations to estimate exposure limits (ELs; Sec. 4) and dazzle spot sizes (Sec.…”
Section: Introductionmentioning
confidence: 99%